Shadow tyrants [compact disc, unabridged] : a novel of the Oregon files - Cussler, Clive; Morrison, Boyd, 1967- (Cussler, Clive. Oregon files adventures., 2018)
Two rival factions of the descendants of a small group of guards are fighting a mighty battle. Now it's up to Cabrillo and his team of expert operatives to halt both groups' destruction.